ATP-triggered ADP release from the asymmetric chaperonin GroEL/GroES/ADP(7) is not the rate-limiting step of the GroEL/GroES reaction cycle - Tyagi, Navneet K. (2010)
The GroEL/GroES protein folding chamber is formed and dissociated by ATP binding and hydrolysis. ATP hydrolysis in the GroES-bound (cis) ring gates entry of ATP into the opposite unoccupied trans ring, which allosterically ejects cis ligands. While earlier studies suggested that hydrolysis of cis ATP is the rate limiting step of the cycle (t(½) ~10s), a recent study suggested that ADP release from the cis ring may be rate-limiting (t(½) ~15–20 sec). Here we have measured ADP release using a coupled enzyme assay and observed a t(½) for release of ≤4–5 seconds, indicating that this is not the rate-limiting step of the reaction cycle.